The Transient Receptor Potential Vanilloid 4 Channel and Cardiovascular Disease Risk Factors - Goto, Kenichi; Kitazono, Takanari (Frontiers in Physiology, 2021)
Vascular endothelial cells regulate arterial tone through the release of nitric oxide and other diffusible factors such as prostacyclin and endothelium derived hyperpolarizing factors. Alongside these diffusible factors, contact-mediated electrical propagation from endothelial cells to smooth muscle cells via myoendothelial gap junctions, termed endothelium-dependent hyperpolarization (EDH), plays a critical role in endothelium-dependent vasodilation in certain vascular beds. A rise in intracellular Ca2+ concentration in endothelial cells is a prerequisite for both the production of diffusible factors and the generation of EDH, and Ca2+ influx through the endothelial transient receptor potential vanilloid 4 (TRPV4) ion channel, a nonselective cation channel of the TRP family, plays a critical role in this process in various vascular beds. Emerging evidence suggests that the dysregulation of endothelial TRPV4 channels underpins endothelial dysfunction associated with cardiovascular disease risk factors, including hypertension, obesity, diabetes, and aging. Because endothelial dysfunction is a precursor to cardiovascular disease (CVD), a better understanding of the mechanisms underlying impaired TRPV4 channels could lead to novel therapeutic strategies for CVD prevention. In this mini review, we present the current knowledge of the pathophysiological changes in endothelial TRPV4 channels associated with CVD risk factors, and then explore the underlying mechanisms involved.